An apicobasal gradient of Rac activity determines protrusion form and position - Couto, Africa; Mack, Natalie Ann; Favia, Lucrezia; Georgiou, Marios (Nature Publishing Group, 2017)
Each cell within a polarised epithelial sheet must align and correctly position a wide range of subcellular structures, including actin-based dynamic protrusions. Using in vivo inducible transgenes that can sense or modify Rac activity, we demonstrate an apicobasal gradient of Rac activity that is required to correctly form and position distinct classes of dynamic protrusion along the apicobasal axis of the cell. We show that we can modify the Rac activity gradient in genetic mutants for specific polarity proteins, with consequent changes in protrusion form and position and additionally show, using photoactivatable Rac transgenes, that it is the level of Rac activity that determines protrusion form. Thus, we demonstrate a mechanism by which polarity proteins can spatially regulate Rac activity and the actin cytoskeleton to ensure correct epithelial cell shape and prevent epithelial-to-mesenchymal transitions.